2013
DOI: 10.1084/jem.20130505
|View full text |Cite
|
Sign up to set email alerts
|

Local BLyS production by T follicular cells mediates retention of high affinity B cells during affinity maturation

Abstract: BLyS expression by GC follicular T cells is required for the efficient selection of high-affinity GC B cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 58 publications
3
107
1
Order By: Relevance
“…In contrast to the impaired B cell TACI expression, and in agreement with a recently reported study (34), we determined that the TACI ligand BAFF was significantly increased in the sera of XID mice. This inverse relationship between BAFF and TACI levels is also seen in newborn mice (28) and TACI KO mice (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the impaired B cell TACI expression, and in agreement with a recently reported study (34), we determined that the TACI ligand BAFF was significantly increased in the sera of XID mice. This inverse relationship between BAFF and TACI levels is also seen in newborn mice (28) and TACI KO mice (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that B cell-intrinsic TACI deficiency increases the availability of T cell help. In a recently published article, Goenka et al (30) showed that while the GC lacks BAFF, a TACI ligand, Tfh-derived BAFF contributes to persistence of B cell clones undergoing affinity maturation. Thus, enhanced recruitment of Tfh by TACI-deficient B cells may cause enhanced BAFF production at the T-B cell border, facilitating maintenance of expanded clones and selection of mutated B cells.…”
Section: Resultsmentioning
confidence: 99%
“…An additional signal that may activate the alternative pathway in LZ B cells is stimulation by BAFF (38). Recent work provides evidence that Tfh cells secrete BAFF locally to adjacent LZ B cells (39). Of note, whereas abolishing BAFF secretion by Tfh cells impaired the selection of high-affinity GC B cells, it had no impact on the maintenance of the GC reaction.…”
Section: Discussionmentioning
confidence: 99%